(untitled) (Journal of Philosophy Culture and Political Science, 2024)
This article explores the lesser-known Baikonyr in the Ulytau region of Kazakhstan, shedding light on the cultural landscape of this area that has often been overlooked in scientific discourse. While the more famous Kyzylorda Baikonur has been extensively studied, this research delves into narratives unique to Baikonyr in the Ulytau region. The article focuses on two crucial sections of narratives: those concerning space-related issues and historical heritage. These narratives, collected from local residents and researchers, reflect a diverse cultural landscape and provide intriguing subjects for cultural analysis. To achieve this, the research employs anthropological methods with both quantitative and qualitative approaches. Field research conducted in various localities, including Astana, Zhezkazgan, Zhezdy, Karsakpay, Baikonyr, and Ulytau, was complemented by oral histories, interviews with museum staff, and analyses of archival documents, museum expositions, and media discourses. The study successfully identifies the prevailing themes and interests of the local population regarding space and historical narratives of Baikonyr. Additionally, it draws attention to the variety of methodologies and approaches used to reconstruct the cultural landscape of the area. Furthermore, the study serves to highlight the untapped potential of Baikonyr, providing valuable insights that can contribute to the advancement of socio-humanities. Understanding the cultural heritage and history of Baikonyr can have practical applications, potentially aiding in the development of museum expositions and other means of presenting the cultural heritage of this region. In conclusion, this research fills a crucial gap in the understanding of Baikonyr’s cultural landscape. By exploring the narratives of locals and researchers, the study uncovers unique aspects of the region and emphasizes its significance in cultural and historical contexts. The findings open new avenues for socio-humanities and offer practical implications for preserving and showcasing the cultural heritage of Baikonyr Key words: cultural landscape, narratives, space, history, Baikonyr, Baikonur petroglyphs, Battle of Bulanty. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back